Homozygous Familial Hypercholesterolemia (HoFH) in Saudi Arabia and Two Cases of Lomitapide Use in a Real-World Setting - Mahzari, Moeber (Adv Ther, 2021)
INTRODUCTION: Homozygous familial hypercholesterolemia (HoFH) is a rare, genetic condition in which mutations in key peptides involved in the low-density lipoprotein receptor (LDL-R) pathway result in markedly elevated levels of circulating LDL-cholesterol (LDL-C). Patients are at high risk of developing early-onset atherosclerotic cardiovascular disease with associated mortality risks. Treatment options are extremely limited, and aspects of society and medical care in Saudi Arabia have the potential to increase incidence and limit treatment pathways in HoFH. METHODS: Along with a brief review of the evidence available on HoFH we describe the treatment of two Saudi Arabian patients with HoFH diagnosed and treated in accordance with local clinical practices and with the microsomal triglyceride transferase protein inhibitor lomitapide. RESULTS: HoFH in Saudi Arabia is characterized by problems associated with consanguinity, a lack of access to lipoprotein apheresis, and pressures to proceed to liver transplant. Among the case histories, the first patient was commenced on lomitapide therapy, and underwent a dramatic decrease in LDL-C levels from 16.5 to 2.2 mmol/L (87% decrease). This patient had problems with access to lomitapide and cessation of the drug resulted in rebound in LDL-C to 22 mmol/L. The second patient experienced delayed commencement of lomitapide therapy. Despite a 45% decrease in LDL-C levels from 15.3 to 6.9 mmol/L, the patient died the following year at age 26 years from complications subsequent to cardiovascular surgery. Lomitapide was well tolerated in both patients DISCUSSION: The experience of these two cases highlights the need for prompt, effective, and sustained intervention in HoFH to prevent cardiovascular morbidity and mortality. Lomitapide is an effective therapy for HoFH, and we look forward to improved access to this drug in Saudi Arabia, where there is a chronic unmet medical need in HoFH.